Various Modes of Delivery After a Trial of Labor among Pregnant Women at Term with a Previous One Cesarean Section: Labor among Pregnant Women at Term with a Previous Cesarean Section - Razzaq, Hafsa; Shabbir, Farzana; Perveen, Saima; Jawad, Arooj; Maqsood, Umaira; Aslam, Sana; Jabbar, Amna (Pakistan Journal of Health Sciences, 2026)
The most crucial approach to lowering the increasing prevalence of cesarean sections and related maternal morbidity is vaginal birth after cesarean (VBAC). The need for local evidence to direct clinical practice is highlighted by the fact that TOLAC success varies across populations. Objectives: To identify the rates of various delivery modalities: spontaneous VBAC, assisted VBAC, and repeat cesarean section among women who have undergone a trial of labor following one prior cesarean section and relate them to age, BMI, and parity. Methods: This study was conducted in the Department of Gynecology at Mohtarma Benazir Bhutto Shaheed Medical College/DHQ Teaching Hospital, Mirpur, Azad Kashmir. It was a descriptive cross-sectional study conducted over 6 months. The sample size was 160 with full-term pregnant women with one prior c-section. Consecutive sampling was applied for this study. Data were analyzed using SPSS version 25.0 with a chi-square test (p<0.05). Results: Spontaneous VBAC occurred in 57.5% of women, assisted VBAC in 20.6%, and repeat cesarean in 21.9%. Assisted VBAC was significantly associated with age ≥30 years (p=0.030) and parity (p=0.026), while spontaneous VBAC was significantly related to BMI (p = 0.041). Conclusions: The VBAC success rate was 78.1%, indicating that TOLAC is a safe and effective option for most women with one previous cesarean section. Although age, BMI, and parity influenced modes of vaginal delivery, they did not significantly affect repeat cesarean rates, supporting planned TOLAC to reduce unnecessary repeat cesarean sections and improve maternal outcomes.